DROID Application Sketch Book - Kaplan, Dean.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
Think you have the next great DROID app idea? The DROID Application Sketch Book is an essential tool for any aspiring Android developer. This sketch book makes it easy to centralize and organize your ideas, featuring enlarged DROID templates to write on. Professionally printed on high-quality paper, it has a total of 150 gridded templates for you to draft ideas and doodle designs while providing ample room to make notes and document the app name and screen name. Its lay-flat binding and perforated pages make it flexible and ideal for various uses. This book is an invaluable tool for bringing your next great Android app idea to life!
Keywords: Computer science; Computer Science; Computer Science, general